Past of a quantum particle: old problem with recent controversies - Dajka, Jerzy (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
Time-symmetric formulation of quantum mechanics—the two-state vector formalism—is presented as a tool for studying past behaviour of quantum systems. A role of weak measurement and weak values in the Cheshire Cat effect and a nested (Vaidman) three-path interferometer are discussed. Interpretation of a particle’s faint trace indicating possibility of discontinuous paths of particles passing the Vaidman interferometer is given. Consistent histories are presented as one of alternative approaches. Multitude of controversial issues is briefly reviewed and discussed.
Keywords: two-state vector formalism; weak values; weak measurement; Cheshire Cat effect